2010
DOI: 10.1080/09658211003702163
|View full text |Cite
|
Sign up to set email alerts
|

The effects of free recall testing on subsequent source memory

Abstract: The testing effect is the finding that prior retrieval of information from memory will result in better subsequent memory for that material. One explanation for these effects is that initial free recall testing increases the recollective details for tested information, which then becomes more available during a subsequent test phase. In three experiments we explored this hypothesis using a source-monitoring test phase after the initial free recall tests. We discovered that memory is differentially enhanced for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 17 publications
3
33
1
Order By: Relevance
“…The lack of an effect of testing on PI contrasts with recent findings that testing reduces PI in free recall learning (e.g., Brewer et al, 2010;Szpunar et al, 2008). There are many differences between our experiment and their experiments.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…The lack of an effect of testing on PI contrasts with recent findings that testing reduces PI in free recall learning (e.g., Brewer et al, 2010;Szpunar et al, 2008). There are many differences between our experiment and their experiments.…”
Section: Resultscontrasting
confidence: 54%
“…When the first list was tested, participants were better able to remember the most recent responses (i.e., D > B), but the opposite was true (i.e., D < B) when the first list was not tested. Recent investigations of PI (Brewer, Marsh, Meeks, Clark-Foos, & Hicks, 2010;Szpunar, McDermott, & Roediger, 2008) have shown that testing decreases PI in free recall learning. In contrast to experiments showing testing effects on PI, we only tested filler items, not the critical items that were used to examine the effects of PI.…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, our results show that the testing effect on source memory is not a universal phenomenon (see also Brewer et al, 2010), and even more importantly, they highlight that variations in the complexity of the source test can produce empirical outcomes that suggest dramatically different, even opposite, conclusions. This complexity component is oftoverlooked in research on source monitoring (for notable exceptions, see Dobbins & McCarthy, 2008;Dodson & Johnson, 1993;R.…”
Section: Resultsmentioning
confidence: 82%
“…In multi-list learning experiments, testing has repeatedly been found to augment later source retrieval. For example, testing can facilitate recollection of contextual information (Brewer, Marsh, Meeks, Clark-Foos, & Hicks, 2010;Chan & McDermott, 2007;Verde, 2004) and can insulate against the buildup of proactive interference (Jang & Huber, 2008;Pastotter, Schicker, Niedernhuber, & Bauml, 2011;Robbins & Irvin, 1976;Szpunar, McDermott, & Roediger, 2008). Pastotter et al proposed that testing promotes temporal (or list) segregation because performing retrieval between study cycles produces internal context change.…”
Section: Importance Of Source Complexitymentioning
confidence: 99%
“…They have found that testing can yield better retention in the long run than restudying (Karpicke and Roediger 2007;Larsen et al 2013). One explanation offered for the testing effect is that it consolidates learning by strengthening the memory trace (e.g., Brewer et al 2010). Recent findings of a repeated testing effect on transfer items further suggest that there can also be a contribution to deep learning (e.g., Butler 2010;Dirkx et al 2014;McDaniel et al 2013).…”
Section: Demonstration-based-training (Dbt)mentioning
confidence: 99%